2022
DOI: 10.31219/osf.io/jtdnz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular detection of monkeypox and related viruses – Challenges and opportunities

Abstract: The recent widespread emergence of monkeypox, a rare and endemic zoonotic disease by monkeypox virus (MPXV), has made global headlines. While transmissibility (R0 ≈ 0.58) and fatality rate (0-3%) are low, as it causes prolonged morbidity, monkeypox is leading to considerable public health anxiety. Thus, effective containment and disease management require quick and efficient detection of MPXV. In this bioinformatic overview, we summarize the numerous molecular tests available for MPXV, and discuss the diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…TNFR and C3L are typically utilized to discriminate between the Congo and west-African clades of MPXV, while HA and ATI are common gene targets. 114 Certain research studies also have pointed out that p38 and possibly p38-MAPK signaling is crucial in Congo Basin MPXV infections. 121 It was observed that increased p38 phosphorylation is a consequence of Congo Basin MPXV infection, and therapy with the p38 inhibitor SB-202190 reduced Congo Basin MPXV viral yields by 9.5 times more than those of West African MPXV.…”
Section: Recognized Gathering Of Genes In Mpxvmentioning
confidence: 99%
See 1 more Smart Citation
“…TNFR and C3L are typically utilized to discriminate between the Congo and west-African clades of MPXV, while HA and ATI are common gene targets. 114 Certain research studies also have pointed out that p38 and possibly p38-MAPK signaling is crucial in Congo Basin MPXV infections. 121 It was observed that increased p38 phosphorylation is a consequence of Congo Basin MPXV infection, and therapy with the p38 inhibitor SB-202190 reduced Congo Basin MPXV viral yields by 9.5 times more than those of West African MPXV.…”
Section: Recognized Gathering Of Genes In Mpxvmentioning
confidence: 99%
“…Particularly, the TNFR (also known as J2R) gene appears to be a promising target for the precise detection of MPXV. TNFR and C3L are typically utilized to discriminate between the Congo and west‐African clades of MPXV, while HA and ATI are common gene targets 114 …”
Section: Pathobiology Of the Mpxvmentioning
confidence: 99%